Projeto mecânico de um dispositivo para remoção do pino pivotante da caçamba dos caminhões Caterpillar modelo 793D - BORGES, Lorran Nascimento (2019)
The global demand for engineering projects, especially mechanical engineering projects, has required economic aspects, safety and product liability considerations. Currently there are many resources to assist the designer, source of information (books, articles among others) as well as various computational tools. Device improvement projects to assist the equipment maintenance processes, have presented great advantage to companies that perform maintenance in their environment, such as gain ergonomics for the performers, lower accident rates, as well as cost reduction, since it reduces the number of performers in the activity. In this context, the present work brings the study and development of a device for removing the pivot pin from the dumps of the off-road trucks Caterpillar 793D. Analytical methods and numerical simulations (finite element method) of the designed model were developed with the intuition of treating uncertainties and avoiding structure failures, avoiding high stresses (preventing material flow zone), deformation and buckling, increasing project reliability. Furthermore, from the study of materials science, a material of properties is selected that meets the needs of the system, dimensioning geometric tolerances with adequate safety factors. The analytical results confronted with the numerical simulation results showed very close values, thus validating the numerical model.